Development of Android-Based Early Reading Learning Media - Hapsari, Estuning Dewi; Yuda, Yoga Prisma; Mubarok, Yoga Akmal (Politeknik Ganesha Medan, 2022)
Early reading is a skill that students should have. This skill becomes a provision for the next stage of skills .Learning to recognize letters, especially early reading in Golan Kindergarten during the pandemic, experienced problems. Students feel less interested when the learning process is carried out conventionally. In addition, parents also have difficulties when it comes to delivering material to children. Through the use of android-based learning media, the learning process is expected to attract students. The method developed the Borg & Gall model, which consisted of ten stages. The data collection techniques used include observation, interviews, and questionnaires. Observation is used to find out the learning conditions in schools. Interviews, conducted with teachers to find out the use value of the media created. Meanwhile, the questionnaire is used as a reference to find out the level of needs in schools. The resulting learning media is tested through media expert validation tests and practicality tests. Validation of media experts to assess whether media is suitable for use as an alternative to learning media in schools. Practicality test, used to assess the level of practicality of the resulting medium. The results of media expert validation obtained a percentage of 81.5, stating that the media was valid. The practicality test was 8,262, and the mean score of students was 77. The two results presented that the android-based learning media for early reading was feasible